Estimation of Homocysteine Level in Sudanese Obese, Gezira State, Sudan. Issue 4 (2022) - Abdelazeem, Hala; Mergani, Adil; Mohammed, Yousif Abdelhameed; Ahmaed, Khalid Abdelsamea M.; Nour, Bakri Yousif Mohamed
No abstract available